2011
DOI: 10.1111/j.1439-0426.2011.01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition and feeding patterns of adult shovelnose sturgeon (Scaphirhynchus platorynchus) in the lower Platte River, Nebraska, USA

Abstract: Two-hundred and seven adult shovelnose sturgeon ranging from 450 to 718 mm in length were sampled from June to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Estimating population size.-Sturgeon over 400 mm FL were considered adults (e.g., Rapp et al 2011) or subadults, and sturgeon less than 400 mm FL were not included in the analyses. Length-frequency histograms were assessed to identify any potential size-related gear bias for adult sturgeon.…”
Section: Methodsmentioning
confidence: 99%
“…Estimating population size.-Sturgeon over 400 mm FL were considered adults (e.g., Rapp et al 2011) or subadults, and sturgeon less than 400 mm FL were not included in the analyses. Length-frequency histograms were assessed to identify any potential size-related gear bias for adult sturgeon.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the total number of prey families observed (36) was higher than reports from other river systems (e.g. 21 families in the MMR, Hoover et al 2007;19 families in the Lower Platte River, Rapp et al 2011; 30 families in the UWR, Bock et al 2011). Such discrepancy may be explained by the hydrological characteristics of the river.…”
Section: Discussionmentioning
confidence: 61%
“…For shovelnose sturgeon in RPMA 4 the relationship between d 15 N and FL spanned a narrower range than that in pallid sturgeon and suggested most foraging occurred at a single trophic level for the majority of sampled fish. The similar enrichment of d 15 N signatures between pallid sturgeon and shovelnose sturgeon was unexpected because field studies of shovelnose sturgeon diets in the Missouri and Platte rivers found benthic macroinvertebrates were the dominant prey in all length classes of fish, with piscivory being rare (Held 1969;Modde and Schmulbach 1977;Berry 2002;Braaten et al 2007;Wanner et al 2007;Rapp et al 2011). There was no significant relationship between FL and d 15 N for shovelnose sturgeon in RPMA 3, which was likely due to the truncated size distribution of our samples.…”
Section: Discussionmentioning
confidence: 93%
“…Estimated trophic positions and food habits of multiple life stages obtained through a mixture of SIA and stomach content techniques will allow managers to examine the importance of varying prey taxa to Scaphirhynchus and to identify habitats where important prey taxa may be limiting (Bergman et al 2008;Rapp et al 2011). Additionally, SIA will allow managers to monitor long-term broad-scale changes in riverine food webs and possible implications for long-lived riverine species.…”
Section: Introductionmentioning
confidence: 99%